God and the Atlantic: America, Europe, and the Religious Divide - Irons, Kendra Weddle (Christian scholar's review, 2012)
God and the Atlantic: America, Europe, and the Religious Divide Thomas Albert Howard Published by Oxford University Press in 2011 pp / $ / Amazon Goodreads A new release by Gordon College’s Thomas Albert Howard, God and the Atlantic: America, Europe, and the Religious Divide is a thoroughly researched examination of the contrasting religious paths...